Impact of Artificial Aeromonas hydrophila Infection on Stress Indicator in Hybrid Catfish (Clarias gariepinus x C. macrocephalus) - Koeypudsa, Weena; Jongjareanjai, Malinee; Phalitakul, Sukanya; Punnarak, Porntep (Journal of Mahanakorn Veterinary Medicine, 2020)
Hybrid catfish (Clarias gariepinus x C. macrocephalus), 11.4±2.8 g in body weight and 12.4±0.9 cm in body length, were submitted to stress analysis in a laboratory. This research was composed of two experiment groups. The first group injected Aeromonas hydrophila into intraperitoneum for inducing acute stress that was a one-day experiment. Another group induced chronic stress that was a four days experiment, by injecting A. hydrophila into intraperitoneum. All catfish were drawn from the caudal vein before and after A. hydrophila injection. Fish with acute stress had blood taken at 0, 3, 6 and 24 hr. Chronic stressed fish had blood taken at the 1st, 2nd, 3rd, 4th day. The catfish blood was investigated for stress indicator indices. These were blood clotting time, cortisol, glucose, osmolarity, plasma electrolytes (Na+, K+, and Cl-). Blood clotting time and cortisol from the control group had no significant differences (P>0.05). Osmolarity in both the acute and chronic bacterial stressed were significantly different (P<0.05). Plasma electrolytes from the control group were stable. Blood glucose from acute and chronic infection indicated statistically significant differences (P<0.05). Moreover, the results revealed that the catfish in the control group were not stressed. Infected fish that are induced to acute and chronic A. hydrophila infection will have problems with blood sugar. In acute stress caused by A. hydrophila infection, the catfish were subjected to hyperglycemia. Hypoglycemia was found in fish when exposed to chronic infection stress.